Time division multiple access-based scheduling algorithm for quality of service enhancement in IEEE 802.11s wireless mesh networks - Mohammed, Abdulnasser Ahmed (2021)
Many challenges face the next generation of wireless communication systems that need to be bound to coexist with each other. The quality of service (QoS) and the performance restrictions are some of them which occur in TDMA in a multi-hop environment. There have been researches and standardization efforts to apply QoS at Media Access Control (MAC) layer. However, the significant performance parameters will directly impact the preparation of the information for the MAC layer before any schedule is run. The particular objective of this is the QoS and performance restrictions in wireless mesh networks based on IEEE 802.11s. Consequently, the degradation of QoS in the network would occur in packet delay and packet loss. Packet delay occurs during the transmission process, where stations may release an Access Point (AP) through which they are connected and join another. Packet loss occurs when it has to wait for an excessive length of time and in the case of real-time streaming like video, where keeping them will not be useful and will only cause further delays to the subsequent packets, which adversely affects the QoS. Power consumption is another important metric that can be affected due to ‘idle listening’, which happens when a station is neither transmits nor receives ongoing communication through the shared medium. In particular, this thesis presents the scheduling of packets in multi-hop wireless mesh networks based on IEEE 802.11s. Two primary aspects are gathering the network information and how the information is used upon scheduling. This study introduces Enhanced Dynamic (ED-TDMA) to exchange the information between Stations (STAs) and Mesh Access Point (MAP), where the overlapping of the coverage area occurs. The utilization of this information follows this to support all the scheduling operations. During the first operation, information on the STAs in the neighboring network is provided from the MAPs. Next is, deciding the available STAs through the network side, followed by taking traffic type into account. The first procedure is Optimum Dynamic Reservation (ODRTDMA). It serves video users with packet delays higher than the threshold set in the network, thus maintaining its QoS. It reduces 15% of the packet loss and 17% of the average delay. It also increases throughput by 7%. The second procedure is High Priority Optimum Dynamic Reservation (HPODR-TDMA). It extends ODR-TDMA by giving STAs having higher delays than the higher delay threshold classified into three classes. Class I users experience a smaller packet loss and higher throughput compared to other classes. It succeeds in reducing the packet loss by 19% and increases throughput by 9%. The third Enhanced Peer Specific Power Saving Mode (E-PSPSM) focuses on power saving by switching between light sleep mode and deep sleep mode techniques. It decreases the power consumption in deep sleep mode by an average of 13%, the average delay by 16%, and increases throughput by 14 %. All these are achieved by way of the enhancement of the information exchange between STAs and MAPs. Subsequently, ODR-TDMA has the best performance in minimizing the packet delay while HPODR-TDMA gives the best performance in reducing packet loss and increasing throughput, and finally, E-PSPSM is the best in reducing power consumption.